2023
DOI: 10.1002/fsn3.3189
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and functional properties of the protein–starch interaction in Chinese yam

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…The decreasing value of viscosity is due to the formation of amylose inclusion complexes between protein and amylose from starch [ 31 ]. This result is in agreement with that of a study by Shao et al [ 35 ], which showed that yam powders with the highest protein ratio had the lowest viscosity.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The decreasing value of viscosity is due to the formation of amylose inclusion complexes between protein and amylose from starch [ 31 ]. This result is in agreement with that of a study by Shao et al [ 35 ], which showed that yam powders with the highest protein ratio had the lowest viscosity.…”
Section: Resultssupporting
confidence: 94%
“…The addition of collagen peptide was responsible for the decreased value of hardness. Increased protein in the starch slowed down the process of water absorption and the swelling of starch, making the IFRC softer [ 35 ]. This is in agreement with the result reported by Shim and Lim [ 9 ], in which mixed-grain porridges with high protein had significantly ( p < 0.05) lower values of hardness as compared to plain rice congee.…”
Section: Resultsmentioning
confidence: 99%
“…Taro peel [2] Palmyrah [3] Potato (Solanum tuberosum) white lioness variety [6] Yam (D. cayenensis, D. dumentorum, y D. bulbifera) and taro (X. maffa Scoth)…”
Section: Dioscoreasmentioning
confidence: 99%
“…Chinese yucca [3] Taro (Colocasia esculenta L. Schott) [17] Yucca, yam, taro, and others [37] Pachyrhizus ahipa [26] Purple yam (Dioscorea trifida)…”
Section: Use Of Solventsmentioning
confidence: 99%
See 1 more Smart Citation